A Simple Electronic System of Security for a 24-Hour Grocery Store - agung kridoyono (Universitas Nahdlatul Ulama Surabaya, 2023)
Grocery stores, commonly found in cities, represent the latest model of retail establishments offering a diverse range of daily essentials and groceries while operating 24/7 for added convenience. However, these stores often encounter security challenges, such as employee lapses like falling asleep or leaving their posts unattended, which can jeopardize safety. To address this issue, we have developed a simple yet effective tool to enhance store security, utilizing an analysis of detection and sensor error rates. This security system relies on analog circuits to process signals from motion sensors, triggering a buzzer notification upon detecting movement. Through this research, the aim of the research is to quantify the level of detection accuracy and sensor error magnitude, as well as determine the optimal sound level for the generated notification. The results of this research contribute to bolstering safety and vigilance in these grocery stores.